The way to business competitiveness: the importance of diversity management and teamwork climate in stabilizing of employees - Jankelová, Nadežda; Joniaková, Zuzana; Procházková, Katarína (Journal of Business Economics and Management, 2022)
Focusing on utilization of employees strengths at workforce brings companies benefit to the diverse workforce and creates a competitive advantage in a turbulent and dynamic business environment. The intention of this research is to fill a significant research gap in the in-depth exploration of relationships and support mechanisms for diversity management. The research is focused on teamwork climate as a mediating variable, moderating the effect of best practices in the implementation of diversity management and on its potential level of influence on the employee turnover in the company. It was applied the correlation to evaluate connection r among criteria of three areas: best practices in diversity management, teamwork climate and employee turnover rates. The control variables were age, gender, education and length of manager practice. The dependency between best practices in diversity management and employee turnover, which is mediated by teamwork climate, has been confirmed. However, partial mediation was found, where only part of the effect is mediated. The rate of turnover is influenced by the gender of the manager, age and length of practice. All variables (age, length of experience and gender) are significantly related to the variables of best practices in diversity management and teamwork climate. First published online 24 March 2022